Pendidikan Religius Di Sekolah Dasar Al Amin Sinar Putih - Andriyanti, Yuliana Rifa; Agung Yuwono Putro, Ahmad; Chandrawati, Titi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2024)
The purpose of this study was to analyze, 1) Educational objectives at Al Amin Sinar Putih Elementary School, 2) to analyze Educational Content, 3)Educational Tools, 4)Educators, and 5) to analyze Student at Al Amin Sinar Putih Elementary School. The information sources utilized were school principals, establishments and Al Amin Sinar Putih Elementary School instructors. The analyze method utilized is information decrease, information introduction, and drawing conclusions. The results of this study show that the aim of education at Al Amin Sinar Putih Elementary School is character education which focuses on religious education according to the school’s vision. The content of education is using the national curriculum and the foundation curriculum. Educational tools in the form of physical and non-physical facilities in the form of infrastructure and services. Educators have good qualifications and are superior in their fields, while students have various different characters but are superior in interest in the field of  religion.